Analisis Pengaruh Arus Menyilang (Weaving) Terhadap Kinerja Lalu Lintas Simpang Tak Bersinyal - Mursalim .; Yuada Rumengan; Ray Galfian Panginan (Journal of Applied Civil and Environmental Engineering, 2021)
This research is an exploratory study that discusses the effect of cross-flow (weaving) on the performance of traffic at the intersection without a signal in the city of Makassar with the aim of knowing the value of the degree of saturation and time delay that occurs at the intersection. This research refers to the method of the Indonesian Road Capacity Manual (MKJI) 1997. The data was collected by direct observation at the research location at the junction of Jalan Abdullah Daeng Sirua, Jalan DR. Leimena, and Jalan Inspeksi PAM, Makassar City. The results showed that the average time for traffic delays that occurred at the intersection was 19.59 seconds / pcu, the average time for traffic delays on the main road was 11.23 seconds / pcu, the average time for minor road traffic delays was 26 , 85 seconds / pcu, the average time for the geometrical delay of the intersection is 4.16 seconds / pcu, the average time for the intersection delay is 23.75 seconds / pcu, the average value of the degree of saturation is 0.94 and is included in the category of service level F.